Characterization and effect on skin hydration of engkabang-based emulsions - Abd Ghani, Siti Salwa; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin; Kassim, Anuar; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Ismail, Zahariah (Japan Society for Bioscience, Biotechnology, and Agrochemistry, 2010)
Formulations containing engkabang fat and engkabang fat esters, F10 and E15 respectively were prepared using a high-shear homogenizer, followed by a high-pressure homogenizer. Both formulations were stable at room temperature, at 45 degrees C, and after undergoing freeze-thaw cycles. The particle sizes of F10 and E15 after high pressure were 115.75 nm and 148.41 nm respectively. The zeta potentials of F10 and E15 were -36.4 mV and -48.8 mV respectively, while, the pH values of F10 and E15 were 5.59 and 5.81 respectively. The rheology of F10 and E15 showed thixotropy and pseudoplastic behavior respectively. There were no bacteria or fungal growths in the samples. The short-term moisturizing effect on 20 subjects analyzed by analysis of variance (ANOVA), gave p-values of 7.35 x 10(-12) and 2.77 x 10(-15) for F10 and E15 respectively. The hydration of the skins increased after application of F10 and E15 with p-value below 0.05.